Notes on the mammals from Imbak Canyon Conservation Area - Ong, Kay York; Julia George Kunai; Daniel Pamin; Hisashi Matsubayashi; Henry Bernard; Abdul Hamid Ahmad (2013)
Primary forest sites for biodiversity conservation in Sabah are declining. Therefore, biodiversity surveys in areas where primary forests still exist are of paramount importance. Information derived from such studies are crucial in order to develop sound biodiversity conservation management plans. A brief camera trapping study of six days and nights in a localised area at the southern slopes of the Imbak Canyon Conservation Area in Sabah, supported by direct and indirect observations, revealed a rich mammal community in the surveyed areas. A total of 23 species of small to large-sized mammals from 6 orders and 13 families were recorded. Compared to an earlier study in the same area, the mammal species recorded in the present study included 14 species that are new records for Imbak Canyon. Clearly, Imbak Canyon is an important area for mammal conservation.